The Use of Marketing Communication Tools by DANONE Company - Zdenka Kádeková; Lubica Kubicova (Polityki Europejskie, Finanse i Marketing)
Each company that wants to be successful on the market has to understand the basic principles of effective communication with the market and also should focus on creating an appropriate and balanced communication mix. When communicating with customers, the most important is the basic information about the product and its advantages. Therefore, each company has to strive to communicate clearly, consistently and convincingly. Important is that the various marketing communication tools were collected and combined with respect to the target market segment. The aim of this paper is to assess the current state of marketing communication and trends in the use of communication mix tools with a focus on advertising. The paper deals with both the analysis and assessment of the general impact of advertising on consumer behavior and focuses on "Danone" company and evaluation its advertising policy to customers. Understanding the basic principles of effective communication with the market and also should focus on creating an appropriate and balanced communication mix. When communicating with customers, the most important is the basic information about the product and its advantages. The basis of good corporate communication mix creates the elements such as advertising, public relations, personal selling, sales promotion, direct marketing and event marketing. These are the tools by which the company Danone seeks to achieve its advertising and marketing objectives. In 2011 Danone came with a new campaign: "Oh la la Danette!“ pointing at French recipe and delicious taste of this product. Another really successful products of Danone company is Actimel and Activia. Survey proved, that the ads of Danone company influence more women than men and there is also a strong dependence between age of respondents and trust to the brand. 15 – days test and the decision of respondents about accession to the test of Activia product is largely affected by the economic situation of the consumer. Most of the respondents truly believe the information about positive health impact of Activia product on human body as it is seen in ads on TV.